When Covid‐19 meets conflict: politics of the pandemic response in fragile and conflict‐affected states. (11th November 2021) - Hilhorst, Dorothea; Mena, Rodrigo
Abstract : The Covid‐19 pandemic has magnified existing crises and vulnerabilities, but much remains unknown about how it has affected fragile and conflict‐affected settings. This paper builds on the theory that hazards become a disaster in interaction with vulnerability and response policies, yet often lead to renewed disaster risk creation. It is based on seven case studies of countries worldwide that experienced social conflict at the advent of the pandemic, covering the period from March–August 2020. The findings show that authorities instrumentalised Covid‐19 to strengthen their control and agendas. Responsibility was assumed for lockdowns, but this was not accompanied by care to mitigate their adverse effects. Social conflict shaped the response, as high levels of mistrust in authorities complicated the implementation of measures, while authorities did not support community‐based coping initiatives. Whether Covid‐19 will trigger or exacerbate conflict and vulnerabilities depends on pre‐existing, country‐specific conditions, and how a government and other actors frame the issue and respond.